2012
DOI: 10.1007/s13318-012-0114-9
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of 5-fluorouracil and increased hepatic dihydropyrimidine dehydrogenase activity levels in 1,2-dimethylhydrazine-induced colorectal cancer model rats

Abstract: To investigate the hepatic dihydropyrimidine dehydrogenase (DPD) activity in colorectal cancer (CRC), which is critically important to create a patient-specific dosing regimen, we performed 5-FU pharmacokinetic studies in 1,2-dimethylhydrazine-induced CRC model rats (CRC rats). After rats received 5-FU intravenous (IV) bolus injections, the area under the plasma concentration-time curve (AUC) and elimination half-life (t 1/2) in CRC rats (10.02 ± 0.37 μg h mL(-1), 0.30 ± 0.02 h, respectively) were significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…investigated the distribution of colon‐specific sodium alginate microspheres containing 5‐FU in the gastrointestinal tract, and performed PK and pharmacodynamic (PD) studies in CRC rats . It was reported previously that activated DPD levels in the liver would be induced by CRC and could be evaluated by the measurement of the plasma ratio of UH2/Ura, which is a possible surrogate biomarker of hepatic DPD activity in CRC rats . Moreover, 5‐FU PK and PD studies were conducted using DPD circadian variation in CRC rats and a pharmacokinetic‐pharmacodynamic (PK‐PD) model was developed with the value of the plasma ratio of UH2/Ura determined before 5‐FU treatment, to simulate tumor growth in rats with CRC after 5‐FU treatment .…”
Section: Discussionmentioning
confidence: 99%
“…investigated the distribution of colon‐specific sodium alginate microspheres containing 5‐FU in the gastrointestinal tract, and performed PK and pharmacodynamic (PD) studies in CRC rats . It was reported previously that activated DPD levels in the liver would be induced by CRC and could be evaluated by the measurement of the plasma ratio of UH2/Ura, which is a possible surrogate biomarker of hepatic DPD activity in CRC rats . Moreover, 5‐FU PK and PD studies were conducted using DPD circadian variation in CRC rats and a pharmacokinetic‐pharmacodynamic (PK‐PD) model was developed with the value of the plasma ratio of UH2/Ura determined before 5‐FU treatment, to simulate tumor growth in rats with CRC after 5‐FU treatment .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Tateishi et al () reported that the DPD activity and protein levels in rat models of hepatic failure were higher than those in their controls, although the mechanisms were not clear. In 1,2‐dimethylhydrazine‐induced CRC model rats, the hepatic DPD activity and the plasma UH 2 /Ura ratio were higher than those in the control rats (Kobuchi, Ito, et al, ; Kobuchi, Kuwano, et al, ). Moreover, the DPD activity in human carcinoma cells was higher than that in normal cells (Miyazaki et al, ).…”
Section: Resultsmentioning
confidence: 95%
“…The present study results suggest that the possible increase in the DPD activity with the administration of capecitabine also affects the changes in the Ura and UH 2 plasma levels. Alternatively, repetitive exposure of 5‐FU can suppress the DPD activity, and this can be assessed by the plasma UH 2 /Ura ratio (Kobuchi, Ito, et al, ; Kobuchi, Kuwano, et al, ). In clinical studies on capecitabine, an increase of 5‐FU exposure after multiple administration of capecitabine has been reported, whereas there was no difference in the pharmacokinetics and no clinically significant accumulation of capecitabine and its metabolites (Hyodo et al, ; Saeki et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation